2017
DOI: 10.1007/s40979-017-0017-2
|View full text |Cite
|
Sign up to set email alerts
|

Cheating in a dental practical exam

Abstract: There is increasing attention given to academic integrity across university education and dental schools are not immune to this problem (Andrews et al. J Dent Educ 71; 1027-1039, 2007 Ford & Hughes Eur J Dent Educ 16(1):e180-e186, 2012). While there has been an increasing concern about academic dishonesty in written exams and assignments, there appears to be a false sense of security in the integrity of practical assessments, involving dental procedures on simulated patients. This paper will present a situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Outside of the review, the importance of this is emphasised by cases where cheating has led to a student's repetition of an academic year. The importance of academic integrity is ultimately due to its potential to echo into patient care 48 . The online OSCEs have recognised and actioned this in many forms including the completion of an academic integrity statement 32 ; a recorded “check‐in” process of the surrounding environment ensuring no elicit materials were accessible to the students; and use of software such as “Respondus” to prevent access of any other materials on the device being used for the examination 42 …”
Section: Discussionmentioning
confidence: 99%
“…Outside of the review, the importance of this is emphasised by cases where cheating has led to a student's repetition of an academic year. The importance of academic integrity is ultimately due to its potential to echo into patient care 48 . The online OSCEs have recognised and actioned this in many forms including the completion of an academic integrity statement 32 ; a recorded “check‐in” process of the surrounding environment ensuring no elicit materials were accessible to the students; and use of software such as “Respondus” to prevent access of any other materials on the device being used for the examination 42 …”
Section: Discussionmentioning
confidence: 99%
“…Contract cheating style support is not just limited to written assessments. Currie et al (2017) observed cheating taking place in practical dentistry examinations, where ready-prepared teeth were available for purchase which students could substitute in place of the ones they were meant to be working on during practical assessments.…”
Section: Examples Of Contract Cheating Publications By Disciplinementioning
confidence: 99%
“…Choi (2019) likewise reported cheating behaviour by students at 92.2% at the Korean dental school. While not limited to written examinations or assignments, cheating also has been cited in dental practical exams despite misconceptions of security and academic integrity for the latter (Currie et al 2017).…”
Section: Academic Dishonestymentioning
confidence: 99%
“…Relationship and perspective coding among student data were used to elucidate the themes through an inductive process (Bradley et al 2007). The actual process of coding involved open, axial and selective coding (Corbin and Strauss 2015). Open coding was applied to breakdown the raw data into broad emotive or attitudinal categories of positive, indifferent and oppositional attitude.…”
Section: Analysis Of the Datamentioning
confidence: 99%